Labour in Global Value Chains in Asia
DOI: 10.1017/9781316217382.017
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Global Production: Apple, Foxconn and China's New Working Class

Abstract: Apple's commercial triumph rests in part on the outsourcing of its consumer electronics production to Asia. Drawing on extensive fieldwork at China's leading exporter-the Taiwaneseowned Foxconn-the power dynamics of the buyer-driven supply chain are analysed in the context of the national terrains that mediate or even accentuate global pressures. Power asymmetries assure the dominance of Apple in price setting and the timing of product delivery, resulting in intense pressures and illegal overtime for workers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 15 publications
(16 reference statements)
0
44
0
1
Order By: Relevance
“…In a first step, Fairphone aims to increase the transparency of the production process with the used potential pollutants, which has been already detected to be a critical issue within the paradox tension (5). A comment from the case company was that they try to collect the full material declarations, even though it is challenging, because the actors in the SC share the proof of their compliance with legislations (e.g., REACH and ROHS), but are less open about information that goes beyond this.…”
Section: Environmental Friendly Production Vs Maintaining Of Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first step, Fairphone aims to increase the transparency of the production process with the used potential pollutants, which has been already detected to be a critical issue within the paradox tension (5). A comment from the case company was that they try to collect the full material declarations, even though it is challenging, because the actors in the SC share the proof of their compliance with legislations (e.g., REACH and ROHS), but are less open about information that goes beyond this.…”
Section: Environmental Friendly Production Vs Maintaining Of Productionmentioning
confidence: 99%
“…The production of the devices and sourcing of the required raw materials incurs severe sustainability challenges, such as the use of water, energy and chemicals, the affection of ecosystems and landscapes as well as the emission of flue gases and wastes [2][3][4]. Moreover, social issues, like insufficient wages, long working hours, unpaid overtime and physical punishment, have been reported in mobile phone production facilities located in China and India [5][6][7]. All these issues are further multiplied by the low durability of electronic devices [8] and the poorly used recycling potential in the sector [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…Argenti 2004;Zadek 2004;Chan et al 2013). It should also be noted that recently there have been several special issues of journals devoted to ethical sourcing-related topics.…”
Section: Descriptive Findings Basic Statisticsmentioning
confidence: 99%
“…For example, some local producers have become as powerful as MNCs because of their size, prominent position in a GPN, and/or lack of viable alternatives in a GPN. As a result, MNCs have found that some producers in GPNs are now irreplaceable, and therefore, immune to CSR codes of conduct and auditing efforts (Chan et al 2013). Further, recent research has shown a much more complex and subtle power dynamic between the various parties in GPNs, as well as a decline in MNCs' relative power at various levels of GPNs (Locke et al 2007).…”
Section: The Promise Of Csr Codes Of Conduct and Codes Of Conductmentioning
confidence: 99%